2003
DOI: 10.1200/jco.2003.11.122
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study of High-Dose Fluorouracil Given As a Weekly 24-Hour Infusion With or Without Leucovorin Versus Bolus Fluorouracil Plus Leucovorin in Advanced Colorectal Cancer: European Organization of Research and Treatment of Cancer Gastrointestinal Group Study 40952

Abstract: Neither FU24h + LV nor FU24h prolong survival, relative to bolus FU + LV. Leucovorin increases PFS if added to FU24h, but increases toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
12

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 17 publications
2
56
0
12
Order By: Relevance
“…A phase II study of high-dose 5-FU (2600 mg m À2 ) and FA (500 mg m À2 ), German AIO regimen, has also been reported as a salvage regimen in gastric cancer with partial remissions of 18% and stable disease of 41% (Vanhoefer et al, 1994). The decreased dose of FA (300 mg m À2 ) in our HDFL compared to German AIO regimen may also decrease the toxicity of grade 3/4 diarrhoea (Kohne et al, 2003). Further, results of our in vitro studies have implied that strict avoidance of bolus injection of 5-FU is the key to avoid myelosuppression (Yeh et al, 2000a).…”
Section: Discussionmentioning
confidence: 77%
“…A phase II study of high-dose 5-FU (2600 mg m À2 ) and FA (500 mg m À2 ), German AIO regimen, has also been reported as a salvage regimen in gastric cancer with partial remissions of 18% and stable disease of 41% (Vanhoefer et al, 1994). The decreased dose of FA (300 mg m À2 ) in our HDFL compared to German AIO regimen may also decrease the toxicity of grade 3/4 diarrhoea (Kohne et al, 2003). Further, results of our in vitro studies have implied that strict avoidance of bolus injection of 5-FU is the key to avoid myelosuppression (Yeh et al, 2000a).…”
Section: Discussionmentioning
confidence: 77%
“…Randomized trials have shown that infusional administration of FU/FA improves the tumor response rate (RR), increases time to tumor progression (TTP -in this review, we will make no distinction between TTP and progression-free survival) and marginally improves overall survival (OS) at reduced or similar toxicity (de Gramont et al, 1997;Ko¨hne et al, 2003), and the Mayo regimen should not be used anymore. In many parts of Europe, and increasingly in United States, modulated infusion regimens are preferred; the most commonly used approach is probably the 'de Gramont' regimen that combines FA, bolus FU and prolonged infusion FU (de Gramont et al, 1997;Ragnhammar et al, 2001;Meyerhardt and Mayer, 2005).…”
Section: Principles For Retrieval Of Datamentioning
confidence: 99%
“…Four studies have compared investigational regimens against a Mayo Clinic (Rochester, MN) regimen control arm [13][14][15][16]. In each case, the median OS was not significantly different from control.…”
Section: Bolus or Infusion?mentioning
confidence: 99%